ANALYSIS OF FACTORS AFFECTING THE ABSORPTION OF FEMALE LABOR IN CENTRAL JAWA - Santosa, Abibita Hamdhal; Aisyah, Siti (Universitas Nusa Cendana, 2025)
Women’s participation in the labor market plays a crucial role in advancing economic growth and fostering gender equality, yet it continues to encounter persistent social and structural obstacles. This research seeks to examine the determinants of female employment absorption in Central Java from 2019 to 2023. The analysis applies panel data regression with a Fixed Effect Model (FEM) to capture the influence of each explanatory variable. The study incorporates the Information and Communication Technology Development Index (ICTDI), Provincial Minimum Wage (PMW), Average Years of Schooling (AYS), investment, labor force, and the presence of vocational training centers. Findings reveal that PMW, AYS, labor force, and vocational training centers exert a significant impact on female labor absorption, whereas ICTDI and investment show no meaningful effect. In light of these results, it is recommended that policymakers emphasize equitable wage systems, broaden educational opportunities, encourage women’s participation in the workforce, and reinforce the contribution of vocational training institutions to sustainably enhance competitiveness and the integration of women into the labor market. Keywords: Labor Absorption; Information; Provincial Minimum Wage; Labor Force; Communication and Technology Development Index (IP-ICT); Level of Education; Vocational Training Institutions